The implementation of International Forestry Principles in Malaysia: A critical study / Harjinder Kaur Gurdial Singh - Harjinder Kaur , Gurdial Singh (2005)
Malaysia, a tropical country with a total area of approximately 32.9 million hectares, is very fortunate to be well endowed with a relatively large tract of rich and diverse tropical rainforests which is acknowledged to be amongst the most complex ecosystem in the world. The total forested area in Malaysia as at the end of 2002 was estimated at 62% of the total area.